Exosomal MicroRNAs Derived from Human Amniotic Epithelial Cells Accelerate Wound Healing by Promoting the Proliferation and Migration of Fibroblasts - Bin Zhao; Xiaodong Li; Xiaomin Shi; Xueqin Shi; Wei Zhang; Gaofeng Wu; Xujie Wang; Linlin Su; Dahai Hu (Stem Cells International)
Previous work in our laboratory demonstrated that exosomes derived from human amniotic epithelial cells (hAECs) accelerated wound healing by promoting the proliferation and migration of fibroblasts. It is reported that exosomes, which are carriers of the microRNAs (miRNAs) and proteins, play an important role in the regulation of cell-to-cell communication. However, it is still unclear precisely which molecule or which group of molecules carried within hAEC-derived exosomes (hAEC-Exos) mediated wound healing. Here, we explored purified hAEC-Exos together with either proteinase K (PROse) or RNase A on the effect of fibroblasts and cutaneous wound healing. Our experiments demonstrated that hAEC-Exos were positive for exosomal markers CD9, CD63, and CD81. Also, we found that hAEC-Exos could be internalized by fibroblasts and then stimulated cell migration and proliferation. However, the promotive effect of hAEC-Exos was abolished by pretreating hAEC-Exos with RNase A, not PROse. Importantly, in vivo wound healing assay showed that local injection of hAEC-Exos or PROse pretreated hAEC-Exos at skin wounds significantly accelerated wound healing. Our findings revealed an important role of exosomal miRNAs in wound healing.